How different power grid efficiency scenarios affect the energy and environmental feasibility of a polygeneration system. (15th June 2020) - Roselli, C.; Marrasso, E.; Tariello, F.; Sasso, M.
Abstract: Combined heat and power generation traditionally allows for higher energy performance than separate production of heat and electricity. However, the significant increase of the renewable energy sources contribution in electricity production has spatially and temporally modified the context in which polygeneration systems operate and the energy and environmental profitability of these technologies could be undetermined. In such a situation it seems interesting to investigate the influence of the power grid efficiency variation on the polygeneration systems performance. For this purpose energy and environmental performance of a proposed system based on combined production are compared to those achieved by a conventional system based on separate production. The primary energy demand of conventional and proposed systems due to electricity depends on the efficiency of the national electric energy system features. In this paper, this efficiency is considered to be time-varying (hour-by-hour) and it is further taken into account that the electric system efficiency changes in different regions of the same Country. According to Italian day ahead market of electricity the national territory is divided in 6 zones; two of them (Centre-North zone and Centre-South zone) will be specifically considered and compared hereinafter. The differences that arise in results are also assessed with respect to the case in which national and local average efficiency is taken into account. The environmental analysis is performed considering the average and the time-varying Italian and local electricity emission factors. The results have highlighted that the cogeneration system feasibility depends upon the variability of these factors. Indeed, referring to thermoelectric-based power grid efficiency, only in Centre-North zone is more energetically convenient to produce heat and power by separate production systems. The environmental analysis outcomes have showed the same trend of energy analysis results in all the considered zones underlining that the evolution towards sustainability in Smart Grids requires an integrated approach. Highlights: Separate and combined production of heat and power systems are compared. Dynamic simulations are conducted to perform energy and environmental analyses. Time-varying power grid efficiency and emissions factors are considered. Variable energy and environmental indices in electricity market zones are defined. Sensitivity analysis is performed considering the indicators provided by regulation.